Turkish IR journals through a bibliometric lens - MEHMETCİK, HAKAN (My University, 2023)
© 2023, All Azimuth.All Rights Reserved.This article aims at evaluating three International Relations (IR) journals in Turkey, namely, All Azimuth, Insight Turkey, and Uluslararası İlişkiler Dergisi. The scholarly contributions of these three journals to Turkish IR is worthy of exploration since together they constitute ‘the mainstream’ of Turkish IR journals. To this end, this article applies a bibliometric analysis in surveying all three journals\" publication records in order to provide a general picture of the field in the last decade. When we consider an evaluation of the Turkish IR community, these three journals are also important and represent different sub-groups and interests among Turkish IR scholars. The field orientations and organization of the IR discipline in a given country may be understood by studying the leading journals of the field in that country. With this assumption in mind, this paper attempts to distinguish certain characteristic differences and similarities among these three journals by surveying their materials and authorships using comparative bibliometric analysis. While there are several articles in the literature that discuss the contents of these publications, no comparative bibliometric analysis has ever been conducted on them
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Bilim, Teknoloji ve Toplum; Social Sciences and Humanities; Sociology; Science, Technology and Society; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; Social Sciences & Humanities; International Relations; Turkish IR; Turkish IR Journals